Peningkatan Kapasitas Produksi dan Manajemen Usaha pada UMKM Kentang Mustofa melalui Penerapan Teknologi Tepat Guna dan Digitalisasi Usaha - Rizqi, Vini; Alti, Rahmi Mudia; Putri, Intan Cynara Valentina (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This community service activity aims to improve the production, management, and marketing capacity of Mustofa "Ade Yuli" Potato MSME in North Cimahi. The main problems include traditional production processes, weak financial records, and limited marketing and business legality. The methods used were participatory training, the application of appropriate technology, and management and digital marketing assistance. The results of the activity showed an increase in production capacity of more than 60%, improvements in product hygiene and shelf life, organized financial bookkeeping, and expanded marketing through labeled packaging, PIRT permits, and digital accounts. This program has proven effective in supporting MSME competitiveness while empowering the community's economy.